SPECIFICS OF RENDERING POLITICAL DISCOURSE IN TRANSLATION - Василевська, Тетяна (SWorldJournal, 2026)
Political discourse in English, its linguistic and sociocultural features are constantly in the focus of attention of linguists, since the connection between language and politics is obvious. Political discourse performs the function of attracting attent